Somatic variant detection from multi-sampled genomic sequencing data of tumor specimens using the ith.Variant pipeline - Nicole Maeser; Aziz Khan; Ruping Sun (STAR Protocols, 2023)
Summary: A common technique for uncovering intra-tumor genomic heterogeneity (ITH) is variant detection. However, it can be challenging to reliably characterize ITH given uneven sample quality (e.g., depth of coverage, tumor purity, and subclonality). We describe a protocol for calling point mutations and copy number alterations using sequencing of multiple related clinical patient samples across diverse tissue, optimizing for sensitivity with specificity. The ith.Variant pipeline can be run on single- or multi-region whole-genome and whole-exome sequencing.For complete details on the use and execution of this protocol, please refer to Sun et al. (2017).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.